Implementation and Operational Research: An Integrated and Comprehensive Service Delivery Model to Improve Pediatric and Maternal HIV Care in Rural Africa. (15th December 2016) - Gamell, Anna; Glass, Tracy R.; Luwanda, Lameck B.; Mapesi, Herry; Samson, Leila; Mtoi, Tom; Nyamtema, Angelo; Muri, Lukas; Ntamatungiro, Alex; Tanner, Marcel; Hatz, Christoph; Battegay, Manuel; et al.
Abstract : Background: Strategies to improve HIV diagnosis and linkage into care, antiretroviral treatment coverage, and treatment outcomes of mothers and children are urgently needed in sub-Saharan Africa. Methods: From December 2012, we implemented an intervention package to improve prevention of mother-to-child transmission (PMTCT) and pediatric HIV care in our rural Tanzanian clinic, consisting of: (1) creation of a PMTCT and pediatric unit integrated within the reproductive and child health clinic; (2) implementation of electronic medical records; (3) provider-initiated HIV testing and counseling in the hospital wards; and (4) early infant diagnosis test performed locally. To assess the impact of this strategy, clinical characteristics and outcomes were compared between the period before (2008–2012) and during/after the implementation (2013–2014). Results: After the intervention, the number of mothers and children enrolled into care almost doubled. Compared with the pre-intervention period (2008–2012), in 2013–2014, children presented lower CD4% (16 vs. 16.8, P = 0.08) and more advanced disease (World Health Organization stage 3/4 72% vs. 35%, P < 0.001). The antiretroviral treatment coverage rose from 80% to 98% ( P < 0.001), the lost-to-follow-up rate decreased from 20% to 11% ( P = 0.002), and mortality ascertainment improved. During 2013–2014, 261 HIV-exposed infants were enrolled, and the early mother-to-child transmission rate among mother–infant pairs accessing PMTCT was 2%. Conclusions: This strategy resulted in an increased number of mothers and children diagnosed and linked into care, a higher detection of children with AIDS, universal treatment coverage, lower loss to follow-up, and an early mother-to-child transmission rate below the threshold of elimination. This study documents a feasible and scalable model for family-centered HIV care in sub-Saharan Africa. Abstract : Supplemental Digital Content is Available in the Text.